DETERMINANTS OF KAI ACCESS APPLICATION USER LOYALTY FROM A STUDENT'S PERSPECTIVE USING THE INFORMATION SYSTEM SUCCESS MODEL - Prili Adelvia Donita; Jaka Nugraha; Jiunn -Woei Lian (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2026)
Phenomenon/Issues: As one of the most widely used modes of transportation, train services provided by PT Kereta Api Indonesia (KAI) have adapted to digitalization through the KAI Access application. Although the application offers various convenient services, several issues remain, particularly related to information quality and service quality, which may influence user loyalty among students as a dominant user segment. Purpose: This study aims to analyze the determinants of KAI Access application user loyalty from a student’s perspective using the DeLone and McLean (2003) Information System Success Model. Novelty: This research extends the Information System Success Model by integrating perceived value and intention to reuse as mediating variables in explaining user loyalty within the context of a railway digital service application, specifically focusing on student users. Research Method: This study employed a quantitative approach using a survey of 130 university students. Data were analyzed using Structural Equation Modeling (SEM) with the Generalized Structured Component Analysis (GSCA) technique to examine the relationships among constructs. Result: The findings indicate that information quality and service quality significantly influence perceived value and user satisfaction. Furthermore, perceived value and user satisfaction have a significant effect on intention to reuse, which ultimately reflects user loyalty toward the KAI Access application. Research Contributions: This study contributes theoretically by enriching the application of the Information System Success Model in the context of digital transportation services. Practically, the results provide strategic insights for improving application quality to enhance customer retention and long-term user loyalty.